Pengaruh Air Limbah Industri Tahu Terhadap Laju Pertumbuhan Tanaman Bayam Cabut (Amaranthus Tricolor) - Eko Siswoyo; Joni Hermana (Teknik Lingkungan Universitas Islam Indonesia, 2017)
The concentration of BOD, COD, N, P and K in the tofu industrial waste is very high, therefore without appropriate treatment, it will become one of environmental problem. The recent study aimed to investigate the effect of tofu waste concentration on spinach plant growth. The plant is put in the plastic pot filled by mixed soil and humus and then added by tofu waste (500 mL) with different concentrations from 0% (balnk), 20%, 40%, 60%, 80% and 100%. Parameters such number of leaf, surface of leaf, wet weight of leaf, dry weight of leaf and height of stem were measured after 15, 20, 25, 30, 35 and 40 days. In order to measure the surface area of leaf, gravimetry method was used. The result of the study showed that after 40 days, pure tofu waste (100%) have the best result for all parameters. This result indicated that high amount of organic substances in tofu industrial waste give ositive impact on the spinach growth, therefore it could be considered as fertilizer in the agricultural activities.